Optimalisasi Manajemen Strategi Untuk Menjadikan UMKM Yang Unggul Dalam Persaingan Bisnis - Edy Sulistiyawan; Siti Istikhoroh; Untung Lasiyono; Wira Yudha Alam; Mohammad Afrizal Miradji; Aji Prasetyo (Ekobis Abdimas, 2024)
In the current era of globalization and digitalization, Micro, Small, and Medium Enterprises (MSMEs) face increasingly complex challenges in maintaining and improving their competitiveness. Optimizing strategic management is crucial to ensure that MSMEs can not only survive but also excel in the tight business competition. This study aims to identify and analyze effective management strategies for MSMEs to improve their competitiveness. The research methodology involves qualitative and quantitative analysis through case studies of MSMEs in various industrial sectors. Data were obtained from in-depth interviews with MSME owners, surveys, and internal documentation analysis. Key findings indicate that MSMEs that successfully implement optimal management strategies—such as product innovation, utilization of digital technology, effective human resource management, and targeted marketing strategies—can significantly improve their competitive position. This study concludes that the implementation of strategic management based on a deep understanding of market needs, adaptation to changes in the business environment, and the use of modern technology are key factors in achieving competitive advantage. Practical recommendations for MSMEs include developing market analysis capabilities, improving digital skills, and implementing more structured management practices. By implementing these recommendations, MSMEs are expected to increase their competitiveness and contribute more to local and national economic growth.